Menumbuhkan Kreativitas Matematika melalui Pendekatan Computational Thinking - Putri Anggraini Purba; Ainun Palihah; Nurmila Hidayana; Rosliana Siregar (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This study aims to explain the implementation of computational thinking-based mathematics learning at SMA Negeri 2 Medan. This research is classified as qualitative descriptive research. Data sources used in this study include the learning process, informants from Mathematics teachers of SMA Negeri 2 Medan, teaching modules, and field notes about the learning process based on computational thinking. Data collection techniques include observation, interviews, and document analysis. The results of this study show that computational thinking-based mathematics learning is able to increase teacher creativity in teaching, increase students' thinking to be open to the surrounding environment which is actually closely related to mathematics, and be able to solve problems structurally and computational thinking-based learning gets a good response by students